1991
DOI: 10.1126/science.2011741
|View full text |Cite
|
Sign up to set email alerts
|

An Immunogenic Onchocerca volvulus Antigen: a Specific and Early Marker of Infection

Abstract: Onchocerciasis (river blindness) is a serious health problem and a severe obstacle to social and economic development, especially in Africa. A complementary DNA fragment coding for an Onchocerca volvulus antigen (OV-16) was cloned and expressed in the plasmid vector pCG808fx. Immune responses to this O. volvulus-specific recombinant antigen were detectable in patients with documented onchocerciasis; the antibody response was also detectable at 3 months and at more than 1 year before infection could otherwise b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
112
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(115 citation statements)
references
References 11 publications
3
112
0
Order By: Relevance
“…Low-molecular weight filarial antigens, either isolated from crude worm extracts or produced as recombinant polypeptides, have been proposed for reliable, early serodiagnosis (Weiss & Karam 1989;Lobos et al 1991;Ramachandran 1993), as well as for the classification of different clinical forms of disease (Cabrera et al 1988;Gallin et al 1989). In support, we found a higher specificity of VLMW-OvAg compared to antigens of higher molecular masses.…”
Section: Discussionsupporting
confidence: 79%
“…Low-molecular weight filarial antigens, either isolated from crude worm extracts or produced as recombinant polypeptides, have been proposed for reliable, early serodiagnosis (Weiss & Karam 1989;Lobos et al 1991;Ramachandran 1993), as well as for the classification of different clinical forms of disease (Cabrera et al 1988;Gallin et al 1989). In support, we found a higher specificity of VLMW-OvAg compared to antigens of higher molecular masses.…”
Section: Discussionsupporting
confidence: 79%
“…The 100% sensitivity of our test recorded in four of the five geographic regions tested is an improvement of previous results, 9,[11][12][13]19,26,27 and shows that the combination of both immunodiagnostic antigens into one hybrid protein had a cumulative effect. Currently, we do not have an explanation for the lack of seroreactivity of two Ecuadorian onchocerciasis sera with OvH2 or OvH3.…”
Section: Discussionsupporting
confidence: 67%
“…Therefore, antibody detection assays have been developed using recombinant O. volbulus antigens. [8][9][10][11][12][13][14] Some of these antigens were tested in a multicenter trial organized by the Tropical Diseases Research Program of the WHO that identified highly specific proteins, 15 and high sensitivity of these tests was achieved by combining three proteins in a diagnostic cocktail. 13,16,17 However, these antigens were difficult to produce and the fact that they were expressed as fusions with a carrier protein made it necessary to run parallel tests to rule out antibody reactions with the carrier.…”
Section: Introductionmentioning
confidence: 99%
“…22 The prevalence of immunoglobulin G4 (IgG4) antibodies to Ov-16, a recombinant antigen of Onchocerca volvulus, was used as a measure of infection/exposure in children. [25][26][27] A sample size of 3,000 children is needed to exclude 0.1% antibody prevalence with 95% confidence.…”
Section: Methodsmentioning
confidence: 99%